2013
DOI: 10.1111/josh.12044
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk for School Violence‐Related Behaviors Among Adolescents With Insufficient Sleep

Abstract: BACKGROUND School violence is associated with significant acute and long‐term negative health outcomes. Previous investigations have largely neglected the role of pertinent health behaviors in school violence, including sleep. Insufficient sleep is associated with adverse physical, behavioral, and psychosocial consequences among adolescents, many of which are concurrently implicated in youth violence. This study examined the relationship between insufficient sleep and school violence behaviors in a nationally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 39 publications
1
34
0
1
Order By: Relevance
“…In a sample of almost 500 seventh-grade youth, community violence exposure was associated with lower GPA directly but also indirectly via sleep problems (Lepore and Kliewer 2013). Adolescents who obtain less than 8 h of sleep per night are concurrently more likely than their peers to report carrying a weapon to school, missing school due to feeling unsafe, being threatened or injured with a weapon at school, and being bullied at school (Hildenbrand et al 2013). Longitudinal data also speak to the link between sleep problems and adolescents carrying or using weapons.…”
Section: Neighborhood and Community Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a sample of almost 500 seventh-grade youth, community violence exposure was associated with lower GPA directly but also indirectly via sleep problems (Lepore and Kliewer 2013). Adolescents who obtain less than 8 h of sleep per night are concurrently more likely than their peers to report carrying a weapon to school, missing school due to feeling unsafe, being threatened or injured with a weapon at school, and being bullied at school (Hildenbrand et al 2013). Longitudinal data also speak to the link between sleep problems and adolescents carrying or using weapons.…”
Section: Neighborhood and Community Factorsmentioning
confidence: 99%
“…Multiple mechanisms are likely implicated in the association between violence exposure (either in the home or in the community) and adolescent delinquency Becker 2010, 2015), but studies have yet to separate out sleep disturbances from other symptoms of PTSD when examining the link between trauma/PTSD and delinquency or other antisocial behaviors. Given the findings summarized above linking sleep to carrying/using a weapon (Hildenbrand et al 2013;Umlauf et al 2011), as well as other studies showing short sleep duration to be associated with violence towards others, truancy, and a criminal record for theft (Yen et al 2010), it would behoove researchers to consider the specific role of sleep problems as one possible mechanism linking trauma and violence exposure to delinquency and other externalizing behaviors. Indeed, there is preliminary cross-sectional evidence suggesting that sleep problems may account for the link between community violence and delinquency in at-risk Latino adolescents .…”
Section: Neighborhood and Community Factorsmentioning
confidence: 99%
“…Interest was sparked by studies showing that sleep loss is related to diminished behavioural response inhibition, increased irritability and hostility and negative affective states which, in turn, are related to aggression and violence (Ireland and Culpin, 2006). Several recent large epidemiological studies have found a link between adolescent delinquency and sleep problems (Catrett and Gaultney, 2009), insufficient sleep amount (Clinkinbeard et al, 2011;Hildenbrand et al, 2013;Meldrum et al, 2015;Peach and Gaultney, 2013) or both (Meijer et al, 2010). However, unanswered questions remain.…”
Section: Introductionmentioning
confidence: 99%
“…Lo anterior resulta preocupante para la comunidad científica y educativa debido a su elevada prevalencia en estudiantes de educación secundaria a nivel mundial (4). De hecho, desde hace tiempo, en Latinoamérica existe una preocupación por los comportamientos violentos juveniles (5).…”
unclassified